Evaluation of the rotor eccentricity added radial force of oscillating water column. (15th May 2023) - Tao, Ran; Lu, Jiahao; Jin, Faye; Hu, Zilong; Zhu, Di; Luo, Yongyao
Abstract: Oscillating water column is a commonly used device for ocean wave energy utilization. Its axial-flow rotor with cantilever blades will be affected by additional radial force because of rotor eccentricity. In this study, eccentric and non-eccentric cases of an oscillating water column are comparatively studied to evaluate this additional radial force characters. Computational fluid dynamics simulations are conducted with experimental data verification. Results show that rotor eccentricity will not obviously influence the efficiency but will generate strong extra radial force. The dominant frequency of radial force becomes rotor rotation frequency and stator interference frequency instead of the rotor blade passing frequency in the non-eccentric case. This is because of the non-uniform distribution of pressure in the uneven tip leakage when rotor becomes eccentric. The evaluation of the amplitude, frequency and generating mechanism of the rotor eccentricity added radial force will be helpful for oscillating water column in avoiding potential accidents. Highlights: The multiplication of radial force of OWC rotor caused by rotor eccentricity is compared. The frequency spectrum of the additional radial force of the rotor eccentricity are decomposed and analyzed. The pressure distribution inside the clearance is compared in detail for eccentric case and non-eccentric case.